The Organized Muse? Organization Theory and "Mediated" Music - Deaville, James (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1997)
Throughout musical history, organizations have occupied a significant role in the production of music. The article explores how scholarship might approach the study of musical organizations through organization theory. After a discussion of modernist and postmodern paradigms in organization theory, the article applies those principles, as well as the thought of sociologist Pierre Bourdieu, to two case studies from the history of the New-German movement. The case studies illustrate how organization theory helps explain the failure of the Euterpe-Verein in Leipzig on the one hand, and the success of the Allgemeiner Deutscher Musikverein on the other.